Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Virgin Coconut Oil bagi Anggota Kowunat Palu - Sitti Sabariyah; Spetriani Spetriani; Siti Fathurahmi (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
Virgin Coconut Oil (VCO) is pure oil that is processed from coconuts and has various benefits, especially for health. VCO processing can be done easily and simply. Using appropriate technology can provide added value and a long shelf life for VCO. The potential of coconut  as the main raw material for making VCO is also considered quite good in the Central Sulawesi region. So the training on making VCO with the target group of Kowunat partners is very appropriate to carry out. In general, the purpose of this service is to provide knowledge and skills to Kowunat partners regarding the benefits of VCO for health and how to make and process VCO. This service is carried out through several stages, namely preparation for implementation, demonstrations of making VCO, presentation and discussion of VCO material and evaluation of training activities. The training was held for 2 days on March 24-25 2022 and was attended by 20 Kowunat members. The 100% attendance and enthusiasm of Kowunat members in the training activities indicated that this activity was successfully carried out. VCO from the training on the second day was 3 liters which was then divided into small plastic bottles of 100 ml.